Assigning F-words as ingredients of interventions for children with cerebral palsy functioning at GMFCS IV and V: A scoping review protocol - Longo, E.; Monteiro, R.; Hidalgo-Robles, Á.; Paleg, G.; Shrader, C.; De Campos, A. C. (Frontiers in Rehabilitation Sciences, 2023)
Introduction: Children with Cerebral Palsy (CP) functioning at Gross Motor Function Classification System (GMFCS) levels IV and V require “on time” identification and intervention. Interventions offered continue to be a challenge, in high-, but even more so in middle-, and low-income countries. Aim: To describe the methods developed to explore the ingredients of published studies on early interventions in young children with cerebral palsy (CP) at highest risk of being non-ambulant based on the “F-words for child development framework” and the design of a scoping review exploring these ingredients. Method: An operational procedure was developed through expert panels to identify ingredients of published interventions and related F-words. After sufficient agreement among researchers was reached, a scoping review was designed. The review is registered in the Open Science Framework database. The 'Population, Concept and Context' framework was used. Population: young children (0-5 years with CP and at highest risk for being non-ambulant (GMFCS levels IV or V); Concept: non-surgical and non-pharmacological early intervention services measuring outcomes from any ICF domain; Context: studies published from 2001-2021. After duplicated screening and selection, data will be extracted and quality will be assessed with the American Academy for Cerebral Palsy and Developmental Medicine (AACPDM) and Mixed Methods Appraisal (MMAT) tools. Results: We present the protocol to identify the explicit (directly measured outcomes and respective ICF domains) and implicit (intervention features not explicitly intended or measured) ingredients. Conclusion: Findings will support the implementation of the F-words in interventions for young children with non-ambulant CP.